Siliceous microfossils as a potential age marker for the early Hirnantian Mass Extinction horizon in South China. Issue 1 (2nd January 2021) - Wu, Xuejin; Luo, Hui; Zhang, Yuandong; Li, Chao
Abstract: Abundant cone-shaped siliceous microfossils have been recovered from Upper Ordovician black shales of the Wufeng Formation in South China. They occur in the Hirnantian Metabolograptus extraordinarius Biozone. An investigation of their internal structure conducted using focused ion beam-scanning electron microscope (FIB-SEM) and transmitted light microscope shows that the specimens are possibly composed of three parts: cephalis, thorax and foot. Robust, longitudinal costae are developed, sometimes branching at the thorax. The geological distribution of these microfossils in South China indicates that they occurred in a restricted epicontinental sea on the Upper Yangtze Platform, which was connected to the open ocean in the north. It seems likely that these microfossils have a limited temporal range relative to the Late Ordovician Mass Extinction (LOME) in the early Hirnantian. In the absence of coeval graptolites or other index fossils, their occurrence therefore provides an age marker for the LOME, and has utility for future shale gas exploration in the Wufeng Formation. Xuejin Wu [xjwu@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, Nanjing, 210008, PR China; University of Science and Technology of China, Hefei, 230026, PR China; *Hui Luo* [huiluo@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, Nanjing, 210008, PR China; *Yuandong Zhang [ydzhang@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, Nanjing, 210008, PR China; University of Chinese Academy of Sciences, Beijing, 100049, PR China; Chao Li [chaoli@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, Nanjing, 210008, China; University of Chinese Academy of Sciences, Beijing, 100049, PR China.